2015
DOI: 10.1200/jco.2014.57.3287
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Communication Skills to the Workplace: Impact of a 38-Hour Communication Skills Training Program Designed for Radiotherapy Teams

Abstract: The 38-hour training program facilitated transfer of team member learned communication skills to the clinical practice and improved patients' satisfaction with care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…For breast cancer patients and for patients with other cancer entities, it was shown that the HRQL is prognostic for and predictive of survival [31,32,35,36,37]. Psychological support as part of palliative care has become an indispensable factor in palliative cancer treatment [38] and, recently, effective transfer and optimization of communications skills were shown [39]. …”
Section: Discussionmentioning
confidence: 99%
“…For breast cancer patients and for patients with other cancer entities, it was shown that the HRQL is prognostic for and predictive of survival [31,32,35,36,37]. Psychological support as part of palliative care has become an indispensable factor in palliative cancer treatment [38] and, recently, effective transfer and optimization of communications skills were shown [39]. …”
Section: Discussionmentioning
confidence: 99%
“…Most of the communication exchanges were mainly centered on medical and radiotherapy contents. The changes observed seem however to be meaningful for patients as patients who have encountered the members of the trained teams have been shown previously to be more satisfied with nurses interventions [19]. There is therefore still a need for improvement.…”
Section: Discussionmentioning
confidence: 90%
“…In the first study, the training of radiation oncologists resulted in an increase in patients' participation in the initial radiation oncology consultations [18]. Second, in previously published results of the present study, completion of the training program allowed the team members to transfer their learned communication skills within the context of radiotherapy planning appointments and patients' satisfaction with their care was improved [19].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…There is evidence also for its translation into the workplace (Lienard et al, 2010;Merckaert et al, 2015;Van den Eertwegh et al, 2013), and in this context, the lack of literature available for CST in psychiatry does not constitute a lack of efficacy. Rather, it reflects the lack of available literature in this growing field and the need for quality and consistency in reporting.…”
Section: Summary Of Evidencementioning
confidence: 99%